Human capital in the nursing management of hospitals - Cordeiro,Ana Lúcia Arcanjo Oliveira (2017)
Abstract OBJECTIVE To analyze how the components of human capital are used in the nursing management of hospital organizations. METHOD This was an exploratory and qualitative study. Data collection took place between October 2014 and May 2015 using semi-structured interviews. The data were analyzed according to content analysis. RESULTS Twelve nurse managers participated. The components of human capital used by the nurses in personnel management were: during the hiring process, when requiring specialized education in the field and prior professional experience; when retaining talents with promotion strategies; in building capacities of professionals through support and training; and in collective work to construct processes and outcome assessment. CONCLUSION The components of human capital need to be managed strategically with a focus on professional skills and development, with the aim of transforming individual and collective knowledge into new technology.